Prognostic value of admission anemia in patients with COVID 19 in Tishreen University Hospital - بكداش, هديل; مالك حجازية; فراس حسين (Latakia University Journal -Medical Sciences Series, 2023)
Background: Coronavirus disease 2019(COVID-19) has rapidly become one of the leading causes of global mortality and morbidity, and whether outcome is modulated by presence of anemia, which have been shown to worsen outcome of COVID-19, is unclear. Aim: The purpose of this study was to determine the effect of presence anemia on the final outcome of COVID-19 patients. Materials and Methods: This was an Observational Retrospective Cohort study involved 597 patients with proven diagnosis of COVID-19 admitted at quarantine unit, Tishreen University Hospital, Lattakia, during the period between April 2020- April 2021. Patients were divided into two groups: group 1 included patients with anemia (389 patients), and group 2 included patients without anemia (208 patients). Results: Out of 597 patients, 357 were male and 240 were female, with mean age of the patients was 63.1±14.2. There were no significant differences between two groups regarding of age, gender, and comorbidities except of hypertension and diabetes mellitus which were more frequent in patients with anemia(p<0.05). There were significant differences between two groups regarding laboratory investigations: Wight blood cell WBC, CRP, and D-dimer which were higher in patients with anemia(p<0.05). Presence of anemia was associated with a higher risk for mortality (OR: 2.5[1.9-4.2], p:0.001), admission in intensive unit care ICU (OR: 9.2[2.7-18.6], p:0.0001), need for mechanical ventilation (OR: 4.2[2.1-13.5], p:0.0001), and longer duration of hospitalization (OR: 5.3[3.4-11.2], p:0.0001). Conclusion: The current study demonstrated presence of unfavorable results of anemia on final outcome regarding morbidity and mortality in COVID-19 patients